2021
DOI: 10.1097/jsm.0000000000000718
|View full text |Cite
|
Sign up to set email alerts
|

An Evidence-Based Approach to Casting and Orthosis Management of the Pediatric, Adolescent, and Young Adult Population for Injuries of the Upper Extremity: A Review Article

Abstract: Objective: Review the use of upper-extremity orthoses and casts after injuries to the wrist and hand in the pediatric, adolescent, and young adult population. The common injuries reviewed include pediatric distal radius fractures, scaphoid fractures, metacarpal fractures, mallet fingers, volar plate injuries of the proximal interphalangeal (PIP) joint, and ulnar collateral ligament (UCL) tears of the thumb metacarpophalangeal (MCP) joint. Data Sources: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…Twenty-two publications were included for data extraction (Figure 1). Sixteen studies 6,8,16,[18][19][20][21][22][23][24][25][26][27][28][29][30] related to specific fractures (Table 5), while six studies 14,[31][32][33][34][35] made general recommendations (Table 6).…”
Section: Scoping Reviewmentioning
confidence: 99%
“…Twenty-two publications were included for data extraction (Figure 1). Sixteen studies 6,8,16,[18][19][20][21][22][23][24][25][26][27][28][29][30] related to specific fractures (Table 5), while six studies 14,[31][32][33][34][35] made general recommendations (Table 6).…”
Section: Scoping Reviewmentioning
confidence: 99%
“…Physical therapists who use splinting put emphasis on simplicity, cost accountability, and their wide application such as external fixation or traction after primary surgery, fostering nerve recuperation after repair, as a compensatory measure for a permanent injury. 4,5 The current report emphasizes the convenient effective treatment of hand injuries by removable orthoses after a mass disaster.…”
mentioning
confidence: 90%
“…The use of a brace for stabilisation following DRF has now gained increased interest, and studies have shown high patient acceptance. [3][4][5] There is, however, sparse information on the effect of the use of brace following surgical treatment of DRF in adult patients. 6,7 Self-assessed quality of recovery (QoR) questionnaires evaluating the postoperative course in a multi-dimensional perspective have gained increasing interest.…”
Section: Introductionmentioning
confidence: 99%
“…The use of a brace for stabilisation following DRF has now gained increased interest, and studies have shown high patient acceptance. 3 - 5 There is, however, sparse information on the effect of the use of brace following surgical treatment of DRF in adult patients. 6 , 7 …”
Section: Introductionmentioning
confidence: 99%